Analisa Kerusakan Transmisi Otomatis dengan Metode Failures Mode and Effects Analysis (FMEA) dan Logic Tree Anaysis (LTA) - Sodikin, Jenal; Satria Jati, Unggul; perdana wanti, linda (Politeknik Negeri Cilacap, 2022)
The power transfer system is an inseparable part of a vehicle unit, this component functions as a power source from the engine, increasing the moment generated by the engine according to the needs of the load and road conditions and reversing the rotation. Type As the age of the vehicle, the transmission it uses will be damaged or even fail to function, most automatic transmissions start having problems after the vehicle is used above 100,000 km or on vehicles that are not used in accordance with the provisions and do not carry out maintenance procedures properly, the automatic transmission is damaged. could come sooner. Based on the implementation of the Failures Mode Effects Analysis (FMEA) method which is used to evaluate components in a system by examining the potential failure model to determine the impact that will occur on the component or work system, it is found that the highest Risk Piority Number (RPN) is found in the Seal component. Piston Matic 450, Multiple Clutch/Clutch Pack 360, Selenoid Valve 324. Each potential failure model is classified based on the impact it can have on the success of the system or on user safety by dividing the categories using Logic Tree Analysis (LTA) with the results of most components automatic transmission is included in the type B failure (Outage Problem) where the component causes failure of all or part of the system. Based on the RPN value, the right maintenance is Predictive Maintenance.